2021
DOI: 10.3390/bs11060086
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation: A Potential Treatment for Obesity in Patients with Schizophrenia

Abstract: Obesity is highly prevalent in patients with schizophrenia and, in association with metabolic syndrome, contributes to premature deaths of patients due to cardiovascular disease complications. Moreover, pharmacologic, and behavioral interventions have not stemmed the tide of obesity in schizophrenia. Therefore, novel effective interventions are urgently needed. Repetitive transcranial magnetic stimulation (rTMS) has shown efficacy for inducing weight loss in obese non-psychiatric samples but this promising int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…Specifically, a most recent review speculates that rTMS can effectively reduce excessive food consumption and promote weight loss in SZ patients after citing those recent findings in non-SZ individuals [ 27 ]. For example, three previous pilot RCTs reported that rTMS could reduce the consumption of foods and cause body weight loss in the general population [ 18 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a most recent review speculates that rTMS can effectively reduce excessive food consumption and promote weight loss in SZ patients after citing those recent findings in non-SZ individuals [ 27 ]. For example, three previous pilot RCTs reported that rTMS could reduce the consumption of foods and cause body weight loss in the general population [ 18 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…rMS frequency is considered to be the primary determinant of differential effects in various types of diseases [6]. Generally, clinical rMS has been classified as high-frequency (>5 Hz) and low-frequency (≤1 Hz) [7][8][9]. High-frequency stimulation has an excitatory effect, whereas low-frequency stimulation has an inhibitory effect [10,11].…”
Section: Introductionmentioning
confidence: 99%